2005
DOI: 10.1007/s00109-005-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Increase of fibronectin and osteopontin in porcine hearts following ischemia and reperfusion

Abstract: Following a severe ischemic injury or myocardial infarction, the extracellular matrix (ECM) of the heart is involved in pathophysiological conditions such as dilatation and cardiac dysfunction. Osteopontin (OPN) has been shown to interact with fibronectin suggesting its possible role in matrix organization, stability and wound healing. There is increased expression of OPN in several tissues in response to injury. Therefore, we tested the hypothesis that acute ischemia (2 h), followed by reperfusion (4 h) may i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 44 publications
2
39
0
1
Order By: Relevance
“…Fibronectin has long been known to play an important role in mediating cell adhesion and migration (Larsen et al, 2006). Rapid up-regulation of fibronectin in the infarcted myocardium has been reported previously after MI (Knowlton et al, 1992;Kossmehl et al, 2005). The up-regulation of fibronectin is ahead of collagens, suggesting its involvement in the acute phase of MI (Knowlton et al, 1992).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Fibronectin has long been known to play an important role in mediating cell adhesion and migration (Larsen et al, 2006). Rapid up-regulation of fibronectin in the infarcted myocardium has been reported previously after MI (Knowlton et al, 1992;Kossmehl et al, 2005). The up-regulation of fibronectin is ahead of collagens, suggesting its involvement in the acute phase of MI (Knowlton et al, 1992).…”
Section: Discussionmentioning
confidence: 92%
“…The up-regulation of fibronectin is ahead of collagens, suggesting its involvement in the acute phase of MI (Knowlton et al, 1992). In 5 h after acute MI in pigs, increased expression of fibronectin was found in fibroblast-like cells in the infarct (Kossmehl et al, 2005). Based on these findings, we decided to study whether this particular class of integrins may be responsible for stem cell homing and engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin has been shown to interact with fibronectin and plays an important role in matrix organization and stability. 12 Previous studies also showed that Ang II increases osteopontin expression, and the osteopontin null mice given Ang II infusion have much less cardiac fibrosis and hypertrophy. 22,23 Xie et al 24 showed that the signals for Ang II-induced osteopontin expression also involve oxidative stress and resultant p42/44 MAPK activation.…”
Section: Discussionmentioning
confidence: 98%
“…11 Osteopontin has been shown to interact with fibronectin and plays an important role in left ventricular remodeling. 12 Therefore, we determined the expression of procollagen I, osteopontin, and fibronectin in mice hearts. As shown in Figure 3A, the expression of procollagen I, osteopontin, and fibronectin increased significantly after infusion of Ang II or norepinephrine in the wild-type mice (PϽ0.01 versus salineinfused wild-type mice).…”
Section: Cardiac Remodeling After Sustained Hypertension and Effect Omentioning
confidence: 99%
“…Há relatos sobre o estímulo de OPN durante injúria cardiovascular W|ávâááûÉ | 91 (Kossmehl et al, 2005) e aumento de sua expressão em macrófagos alveolares de pacientes com doença pulmonar obstrutiva (Heguy et al, 2006). Em pacientes com DM2 foi observado expressões gênicas elevadas de Opn (Haug et al, 2014).…”
Section: W|ávâááûé | 86unclassified